Determinants of Frugal Behavior: The Influences of Consciousness for Sustainable Consumption, Materialism, and the Consideration of Future Consequences - Suárez, Ernesto; Hernández, Bernardo; Gil-Giménez, Domingo; Corral-Verdugo, Víctor (Frontiers in Psychology, 2020)
The transition towards sustainability and the adjustment to climate change should involve the reduction of consumption behavior and the need to maintain social practices of frugality. This paper investigates the influences of consciousness for sustainable consumption (CSC), materialism and the consideration of future consequences on frugal behaviors. Four-hundred-and-forty-four individuals responded to an instrument investigating these variables. Results of a structural model revealed that materialism significantly and negatively influenced the three dimensions of CSC: economic, environmental, and social. The consideration of distant future consequences positively and significantly affected the economic dimension of CSC. Frugal behavior received significant and positive influences from the three CSC dimensions and from consideration of distant future consequences. The model explained 46% of variance in frugality, revealing the importance of awareness of the consequences of resource consumption and the consideration of future consequences have on promoting a moderate consumption of resources.